Report of the second regional coordination workshop of GEWAMED - Sagardoy J.A.; Abdellatif M.; Chimonidou D.; Mellouli K.; Quagliariello R.; Tomassini B.; Vassiliou L. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
The objective of this regional workshop was to improve the cooperation, dialogue and knowledge among partners and external organisations interested in the subject of food security, food safety and their link to the gender and water issues. The opportunity of the workshop was also used to review the progress made in the implementation of major activities by the project partners and this proved to be a highly participative session. The subject of food security received more attention than food safety which is to be expected considering that food security is a topic of high relevance in the region. Session 3, dealing with indicators and the establishment of National Central Focal Points, is one of the major outputs of the project and an important mean of communication and dissemination of gender information. Session 4 was dedicated to review the progress in setting up the regional and national websites. The expected results of the meeting were a) to improve the cooperation among partners and external organisations interested in the subject, b) to increase the knowledge of the participants on issues related to food security and safety and the role that women can play in their effective implementation and c) to improve the coordination and collaboration in the implementation of GEWAMED project activities.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)